Perbedaan Ukuran Partikel Terhadap Kualitas Briket Arang Batang Pisang - Erizal Thoyeb; Farida Hanum Hamzah; Yelmira Zalfiatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Banana stem contain beneficial compounds hemicellulose, cellulose and lignin which is quite high but has not been utilized optimally. This research aims to utilize banana stems as the main ingredient in making charcoal briquettes and get good quality briquette formulations. The study was conducted experimentally using a complete randomized design method consisting of 5 treatments and 3 replications to get 15 expremintal unitsand continued with Duncan’s New Multiple Range Test (DNMRT) at level 5%. The treatments in the study were particle size differences as include: 20 mesh, 40 mesh, 60, mesh, 80 mesh and 100 mesh. The parameters observed in this study were water content, vapour content, ash content, bound carbon content, density, fueled power and calorific value. The result of analysis of variance showed that the particle size charcoal dry banana stem had a significant effect on were water content, vapour content, ash content, bound carbon content, density, fueled power and calorific value. Selected treatment was 40 mesh which has water content 5.67%, vapour content 19,49%, ash content 17,66%, bound carbon content 57,17%, density 0.51g/cm3, fueled power 59x10-4 g/sec and calorific value 5304.13 cal/g.Keywords:briquettes, dry banana stem, particle size